Non-financial Reporting: International Context, Russian Practice - СенатороваЕлена Александровна (Journal of Corporate Finance Research / Корпоративные Финансы | ISSN: 2073-0438, 2018)
The main aim of the research is to analyze the existing sustainability accounting and reporting practices, to set up recommendations for improving the sustainability reporting legislation (as a result of author’s participation in the international research project, University of Western Ontario, Canada). Corporate social responsibility has become part and parcel of Russian business. Consequently, the demand to the quality of non-financial accounting and reporting has increased. Detailed analysis of Russian and international experience, assessment of current trends contributes to an improvement of the non-financial accounting and reporting system. The article includes literature review of research in non-financial reporting problematic. Particular attention is paid to current research trends. The paper contains of the acquired analysis and classification of recent themes in non-financial reporting and accounting research. Based on this analysis, we conclude that the general attention should be paid to the improvement of legislation in the field of non-financial reporting regarding the information related to the indexes disclosed in the non-financial reports, capital data, including intellectual capital in term of companies’ sustainable development. The compulsory regulation of non-financial reporting and accounting is required for state companies, joint-stock companies, companies with large sales and assets. According to research, the most advanced form of non-financial reporting is integrated reporting. Conceptual approach to integrated reporting is based on integrated thinking. A systematic approach in the disclosure of non-financial information creates additional opportunities to analyze and improve the various aspects of the economic, environmental and social development for the Russian companies. For this purpose, the development of the detailed legislation background in integrated reporting is required.